Perspective: Vagal nerve stimulation in the treatment of new-onset refractory status epilepticus - Mantoan Ritter, Laura; Selway, Richard (Frontiers in Neurology, 2023)
Introduction: Resistance to drug therapy is a major hurdle in new-onset refractory status epilepticus (NORSE) treatment and there is urgent need to develop new treatment approaches. Non-drug approaches such as neuromodulation offer significant benefits and should be investigated as new adjunct treatment modalities. An important unanswered question is whether desynchronizing networks by vagal nerve stimulation (VNS) may improve seizure control in NORSE patients. Main Text: We present a summary of published NORSE cases treated with VNS and our own data, discuss possible mechanisms of action, review VNS implantation timing, stimulation setting titration protocols and outcomes. Further, we propose avenues for future research. Discussion: We advocate for consideration of VNS for NORSE both in early and late stages of the presentation and hypothesize a possible additional benefit from implantation in the acute phase of the disease. This should be pursued in the context of a clinical trial, harmonizing inclusion criteria, accuracy of documentation and treatment protocols. A study planned within our UK-wide NORSE-UK network will answer the question if VNS may confer benefits in aborting unremitting status epilepticus, modulate ictogenesis and reduce long-term chronic seizure burden.